Determinants of mobile learning systems' adoption in Zimbabwe rural secondary schools - Muzurura, Joe; Chigora, Farai; Mutambara, Emmanuel; Zvavahera, Promise; Ndlovu, Joram (International Journal of Education and Practice, 2022)
In today's technologically-driven educational landscape, mobile learning systems (MBL) have progressively risen to become critical tools for effective education delivery in many rural schools. Like in most developing countries, the education sector in Zimbabwe plays a critical role in facilitating human capital development and economic growth and development. However, the country's rural secondary schools are still lagging behind urban secondary schools in embracing MBLs. The adoption of MBLs could represent a significant breakthrough not only in terms of reducing educational costs but also for providing effective and efficient learning and teaching processes. The adoption and acceptance of MBLs is likely to transform rural secondary school students' lives by enabling them to access cheap education and also to meaningfully contribute to the eradication of poverty and hunger in their communities. The study employed structural equation modelling where data was collected with the aid of a structured questionnaire from 100 randomly selected respondents attending rural schools in Guruve and Chiota Rural Districts. The findings show that the likelihood of adopting or deferring the adoption of MBLs in rural secondary schools is influenced by factors such as perceived usefulness, compatibility, perceived ease of use, social influence, learner and teacher's autonomy, relative advantages and learner awareness. Policies that increase usage of mobile banking learning systems in rural secondary schools especially the reduction in transaction cost, perceived risk, complexity of user interfaces are recommended.